2019
DOI: 10.22146/agritech.44764
|View full text |Cite
|
Sign up to set email alerts
|

Value Chain Analysis on Pigmented Rice: A Case Study in Sleman Regency, Special Region of Yogyakarta, Indonesia

Abstract: White rice has become the main source of carbohydrates, but in the last few years, red and black rice are getting more popular. Red and black rice can be an alternative food for people who wish to reduce the risk of diabetics due to its low glycemic index. Pigmented rice demand in Yogyakarta is continuously increasing. However, farmers are reluctant to plant pigmented rice because of their lower yields. Value chain analysis on pigmented rice is performed to provide the condition of the business’ performance fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 2 publications
(1 reference statement)
0
8
0
Order By: Relevance
“…Even though the price is higher than white rice, consumers' willingness to pay for black rice is around IDR 29,000, while the willingness to pay for red rice was IDR 33,350 per kilogram [17]. On both red and black rice, the highest farmer's share was when on the chain that consisted of the farmer, distributor, and end-user consumer [18]. Even though the price is high, the price of pigmented rice tends to be consistent.…”
Section: Consumers Perspective On the Quality Of Pigmented Ricementioning
confidence: 99%
“…Even though the price is higher than white rice, consumers' willingness to pay for black rice is around IDR 29,000, while the willingness to pay for red rice was IDR 33,350 per kilogram [17]. On both red and black rice, the highest farmer's share was when on the chain that consisted of the farmer, distributor, and end-user consumer [18]. Even though the price is high, the price of pigmented rice tends to be consistent.…”
Section: Consumers Perspective On the Quality Of Pigmented Ricementioning
confidence: 99%
“…The product attributes used for the questionnaire are displayed in Table 2. Black rice packaging includes the cooking method The attributes above are taken from a combination of attributes of pigmented rice which in previous studies have become attributes considered necessary by consumers (Wuryandani, et al, 2018;Anindita, et al, 2019;Putri, et al, 2019). Grain integrity, grain length, and color density are physical attributes consumers consider when buying colored rice.…”
Section: Kano Modelmentioning
confidence: 99%
“…The organic certification process has quite a lot of requirements and is rigid. Several small farmers revealed that the certification process was a problem for them in terms of process and cost (Anindita, et al, 2019).…”
Section: Attractivementioning
confidence: 99%
“…Other parties connect farmers and consumers. The most significant income margin in the pigmented rice business chain consists of farmers, farmer groups, retailers, and end consumers (Anindita, Ismoyowati, & Suwondo, 2019).…”
Section: Pigmented Rice Businessmentioning
confidence: 99%
“…After harvesting, rice is colored only through drying and packaging, without sophisticated and complicated technology. (Anindita et al, 2019;Custodio et al, 2019;Englund, Zhou, Hedrick, & Kraak, 2020;Kathuria & Gill, 2013;Putri & Ismoyowati, 2020)…”
Section: And Rural Development Researchmentioning
confidence: 99%